About Clinical Efficiency of Cryopreserved Human Cord Blood Serum - Prokopyuk, O. S.; Lipina, O. V.; Musatova, I. B. (Problems of Cryobiology and Cryomedicine, 2008)
It has been shown that content of follicule-stimulating and luteinizing hormones, estradiol and progesterone in human cord blood serum (HCBS) significantly higher than in serum of healthy nonpregnant women of reproductive age. In the experiment the cryopreserved HCBS has been shown as not having embryotoxic or teratogenic effect. Unique composition of cryopreserved HCBS preparation determines the capacity of its wide use in clinic and increases treatment efficiency of different pathologies.